Service Implementation Analysis of Adolescent Reproductive Health toward Adolescents’ Expectations and Needs - Rizqi, Yuditha Nindya Kartika; Nafisah, Lulu; Aryani, Aisyah Apriliciciliana (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
Lack of knowledge and information on sexual and reproductive health has led to an increase in reproductive health problems, such as sexual violence and abuse, marriage and teenage pregnancy. There are several government programs related to youth health, but only a few young people can use and take advantage of these programs. This study aims to outline the needs and expectations of adolescents in sexual education and reproductive health. The method used is a qualitative method and an in-depth interview was conducted. Use deliberate sampling techniques to determine samples. The interview results showed that all adolescents had heard of adolescent reproductive health (KRR), but they could not fully explain the definition and scope of KRR. The availability of KRR information and services around the residence is still poor, and although there is no regular schedule and incomplete, most are obtained from the school. The services that young people need include youth-friendly counseling, counseling and health checks. The expected facilities are easy-to-use facilities, affordable costs and flexible service hours. Support from policy makers, plan implementers, schools and youth residential communities are needed to provide youth-friendly and easily accessible KRR services.